Pengaruh Fraksi Lempung Terhadap Nilai Kohesi dan Indeks Plastisitas - Rambe, Renold Pangidoan; Afriani, Lusmeilia; Iswan, Iswan (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2016)
This study aims to see the influence the fraction of clay in the sand by comparing parameters ofstrong shear soil that is resulted from unsoaked and soaked conditions of Direct Shear Test andAtterberg Limit. An increase in the fraction of clay in the sand can change the physical propertiesof the soil and the mechanical properties. An increase in the fraction of clay can also improve thevalue soil cohesion and ground plasticity index but it reduces the value soil friction. Theparameter change magnitude is analyzed by looking at the results of correlation analysis ofcohesion of the soil plasticity index, and some of the physical parameters of the soil. Thecorrelation between the shear test directly with the plasticity index against the physical propertiesof soil clays that linear regression obtained a very strong correlation (0.8 – 1) and limit land thatis used are sand which is already substituted by clays from 0% – 50%.Direct shear test which results from the condition of unsoaked conducted in the laboratoryobtained that addition levels of clay showed an increase in the value of cohesion but the angleshear declined. Direct shear test results from the condition of soaked (soaking 4 days) obtained adecrease of the value of cohesion (c) down and slide angle (φ) which is also affected by soakingthe soil. The test results show the Atterberg limits that a percentage of the original soil andaddition of clays to 20% has no plasticity index value. This is because the ground is still are off(loose soil). As for the addition of clays from the percentage of 30%, 40%, and 50% of the land isincluded soil cohesive and value each PI is 8.87%, 17.7%, and 12.04%.Keywords: direct shear, cohesion, plasticity index